An Efficient Synthesis of 5‐Aminopropargyl‐Pyrimidine‐5′‐O‐Triphosphates Through Palladium‐Catalyzed Sonogashira Coupling. Issue 1 (18th March 2019) - Shanmugasundaram, Muthian; Senthilvelan, Annamalai; Kore, Anilkumar R.
Abstract: The utilization of 5‐aminopropargyl nucleotide serves as a versatile molecular biology tool for the introduction of functional groups into a nucleic acid target of interest by using in‐vitro enzymatic incorporation method. This article describes a simple, reliable, general, and efficient two‐step chemical method for the synthesis of 5‐(3‐aminopropargyl)‐2′‐deoxycytidine‐5′‐ O ‐triphosphate, 5‐(3‐aminopropargyl)‐cytidine‐5′‐ O ‐triphosphate, 5‐(3‐aminopropargyl)‐2′‐deoxyuridine‐5′‐ O ‐triphosphate, and 5‐(3‐aminopropargyl)‐uridine‐5′‐ O ‐triphosphate, starting from the corresponding pyrimidine triphosphate. The first step involves regioselective C ‐5 iodination of pyrimidine triphosphate using N‐iodosuccinimide and sodium azide. In the second step, propargylamine is coupled to the iodo‐pyrimidine using the palladium‐catalyzed Sonogashira reaction, producing good yields of highly pure (>99.5% HPLC) 5‐aminopropargyl‐pyrimidine‐5′‐ O ‐triphosphate. In this approach, the palladium‐catalyzed Sonogashira coupling reaction is highly chemoselective and does not involve protection and deprotection. © 2019 by John Wiley & Sons, Inc.